2022
DOI: 10.20469/ijbas.8.10001-3
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Intrinsic Rewards on Employee Engagement in The Food Industry in Bosnia and Herzegovina

Abstract: The purpose of this study is to research and examine the relationship between leadership styles and job satisfaction of employees in the food industry in Bosnia and Herzegovina. As a quantitative research study, the survey method is used with a developed questionnaire for the primary data collection. The questionnaire is adopted from valid sources, contributing to leadership and job satisfaction worldwide. Using the convenience sampling method, 210 valid responses are obtained and analyzed using the Software P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Several studies such as Jung (2001), Judge and Piccolo. (2004), Aarons (2006), Skopak and Hadzaihmetovic (2022), Jacobsen et al, (2022) provided strong support for the research hypotheses, indicating that individuals in the transformational leadership and nominal group conditions exhibited superior performance compared to those in the transactional leadership and real group conditions. This consistent pattern of results was observed across both measures of creativity.…”
Section: Theoretical Frameworkmentioning
confidence: 67%
“…Several studies such as Jung (2001), Judge and Piccolo. (2004), Aarons (2006), Skopak and Hadzaihmetovic (2022), Jacobsen et al, (2022) provided strong support for the research hypotheses, indicating that individuals in the transformational leadership and nominal group conditions exhibited superior performance compared to those in the transactional leadership and real group conditions. This consistent pattern of results was observed across both measures of creativity.…”
Section: Theoretical Frameworkmentioning
confidence: 67%
“…At the same time, when employees fail to deliver, they do not get salary increases, bonuses other benefits. Thus, we argue it is an exchange relationship (Skopak & Hadzaihmetovic, 2022).…”
Section: Introductionmentioning
confidence: 82%
“…Based on empirical research, Skopak and Hadzaihmetovic (2022) concluded that the "contingent rewards" of transactional leaders and "individualized consideration" of transformational leaders promote job satisfaction. And transactional and transformational leadership promotes job satisfaction and career development.…”
Section: Transactional and Transformational Leaderships And Job Satis...mentioning
confidence: 99%
“…To investigate the evaluation of compensation policies and their impact on employee retention in the food industry, a mixed-methods research approach will be employed (Skopak & Hadzaihmetovic, 2022). This approach combines quantitative and qualitative methods to provide a comprehensive understanding of the topic.…”
Section: Methodsmentioning
confidence: 99%